1973
DOI: 10.1002/pol.1973.170111204
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fine structure on the pyrolysis of cellulose. I. Vacuum pyrolysis

Abstract: synopsisThe effects of crystallinity, orientation and degree of polymerization on the vacuum pyrolysis of cellulose have been investigated. Natural, modified and manmade celluloses were characterized and the kinetics of their pyrolysis a t 251OC studied. The hightemperature pyrolysis of these samples was also investigated by means of DSC and TGA. At 251°C all of the samples showed a rapid, initial weight loss followed by a linear (weight loss)1/2 versus time dependency. Both the initial weight loss and the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 50 publications
4
46
0
1
Order By: Relevance
“…Apparently this temperature is in agreement with the thermogravimetric results on cellulose decomposition [48]. The reaction rate of cellulose decomposition was shown to be inversely proportional to the degree of polymerization and related to the orientation and crystallinity during thermal decomposition in vacuum [49][50][51]. Levoglucosan appears to be produced from the less ordered regions.…”
Section: Pyrolysis Of Macromolecular Biomass Constituentssupporting
confidence: 78%
“…Apparently this temperature is in agreement with the thermogravimetric results on cellulose decomposition [48]. The reaction rate of cellulose decomposition was shown to be inversely proportional to the degree of polymerization and related to the orientation and crystallinity during thermal decomposition in vacuum [49][50][51]. Levoglucosan appears to be produced from the less ordered regions.…”
Section: Pyrolysis Of Macromolecular Biomass Constituentssupporting
confidence: 78%
“…Moreover, thermal stability and heat resistance also have a close relationship with the crystallinity degree. In particular, crystalline regions in cellulose are much more stable than amorphous parts in cellulose [34][35][36] . Therefore, increase of crystallinity degree during chemical treatment also improved the heat resistance of PCNF and CNF_TiO 2 samples.…”
Section: Characterization Of Pure Cellulose Nanofibers and The Nanmentioning
confidence: 99%
“…Briodo et al [87] found that crystalline cellulose and undergoes a large change in DP before weight loss occurs. Similarly, Basch and Lewin [88] proposed that if cellulose depolymerized by an unzipping process then the number of free chain ends, as reflected by DP, will influence the initiation rate. Radlein [46] presented that one cellulose sample which has been heated to 180 o C for several hours and has a very low DP appears to give an abnormally high yield of levoglucosan.…”
Section: Pyran-and Furan-derivatives (C5-6 Ring-contained Compounds)mentioning
confidence: 99%